Interaction of the Adolescent Environment and Learning Achievement - Amidah, Amidah; Mau Manek, Alfridus; Hernawati, Retno; Sasea, Tirtania (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The low learning outcomes at SMA Negeri I Fatuleu are attributed to several factors that hinder learning development. Observations and interviews with Economics teachers revealed that many students still exhibit habits such as lack of attention, difficulty concentrating, frequent daydreaming, and failing to complete assigned homework. Additionally, some students consistently submit assignments late or fail to submit them altogether. This study examines the influence of family environment and peers on learning achievement, with 12 statements for family and 13 for peers, all valid and reliable. A prerequisite analysis was conducted and deemed feasible. Using random sampling, 50 respondents were selected. The study also applies Multiple Regression Analysis and supports various hypothesis tests. The regression analysis shows that the family environment and peers have a positive and significant effect on learning achievement, as indicated by the equation Y = 4.729 + 0.638x1 + 0.427x2. The constant value of 4.729 means that if both variables are zero, Y is 4.729. The family environment's coefficient of 0.638 signifies a significant influence with a Sig. value of 0.008 (<0.05). The study concludes that both family environment and peers positively and significantly influence learning achievement, with family providing motivation and peers offering support and collaboration.